Enhanced pressor response to carotid occlusion in commNTSlesioned rats: Possible efferent mechanisms - Sato, Monica Akemi [UNESP]; Menani, José Vanderlei [UNESP]; Lopes, Oswaldo Ubríaco [UNESP]; Colombari, Eduardo [UNESP] (American Physiological Society, 2000)
Bilateral common carotid occlusion (BCO) over a period of 60 s in conscious rats produces a biphasic pressor response, consisting of an early (peak) and late (plateau) phase. In this study we investigated 1) the effects of lesions of the commissural nucleus of the solitary tract (commNTS) on the cardiovascular responses produced by BCO in conscious rats and 2) the autonomic and humoral mechanisms activated to produce the pressor response to BCO in sham- and commNTS-lesioned rats. Both the peak and plateau of the pressor response produced by BCO increased in commNTSlesioned rats despite the impairment of chemoreflex responses induced by intravenous potassium cyanide. In sham rats sympathetic blockade with intravenous prazosin and metoprolol, but not vasopressin receptor blockade with the Manning compound, reduced both components of BCO. In commNTS-lesioned rats the sympathetic blockade or vasopressin receptor blockade reduced both components of BCO. The results showed 1) the sympathetic nervous system, but not vasopressin, is important for the pressor response to BCO during 60 s in conscious sham rats; 2) in commNTS-lesioned rats, despite chemoreflex impairment, BCO produces an increased pressor response dependent on sympathetic activity associated with vasopressin release; and 3) the increment in the pressor response to BCO in commNTS-lesioned rats seems to depend only on vasopressin secretion.
Keywords: Arterial pressure; Baroreceptor; Chemoreceptor; Nucleus of the solitary tract; Potassium cyanide; Sympathetic; Vasopressin